Inkjet-Printed Reduced Graphene Oxide/Poly(Vinyl Alcohol) Composite Electrodes for Flexible Transparent Organic Field-Effect Transistors - Lim, Soojin; Kang, Boseok; Kwak, Donghoon; Lee, Wi Hyoung; Lim, Jung Ah; Cho, Kilwon (American Chemical Society, 2012)
The characteristics of organic field-effect transistors (OFETs) prepared with inkjet-patterned reduced graphene oxide (RGO)/poly(vinylalcohol) (PVA) composite electrodes were studied. PVA was blended with graphite oxide to enhance exfoliation of the graphite sheets and to provide for stable inkjet printing. Multistep reduction based on a combination of chemical and thermal reduction was conducted to increase the conductivity. Use of the inkjet-patterned RGO/PVA electrodes increased field-effect mobility of the bottom-contact pentacene FETs to 0.23 cm(2)/(V.s), which was significantly enhanced relative to that of FETs with Au or PEDOT:PSS electrodes. Moreover, we successfully prepared all-organic flexible transparent OFETs using inkjet-patterned RGO/PVA electrodes on plastic substrates.
Keywords: THIN-FILM TRANSISTORS; SELF-ASSEMBLED MONOLAYERS; ENERGY-LEVEL ALIGNMENT; GRAPHITE OXIDE; POLYMER; PENTACENE; MOBILITY; AU(111); SHEETS